Towards a mechanistic interpretation of bird migration in South America - Jahn, Alex Edward (2006)
Research to date has demonstrated that bird migration is comprised of highly diverse and plastic behavioural patterns. Our objective is to highlight the importance of studying mechanisms underlying these patterns in austral migrants. We focus on the high incidence of overlap in breeding and non-breeding ranges as a particularly thought-provoking pattern. We then explore the opportunities afforded by partial migration theory to elucidate the mechanisms underlying seasonal range overlap. We propose that a mechanistic understanding of migration in South America will both provide a deeper appreciation of the ecology, physiology and evolution of migratory species in the New World, and improve the scientific foundation for their conservation.